Pengaruh ROA, CR Dan TATO Terhadap Harga Saham Perusahaan Farmasi Yang Terdaftar Di BEI Periode 2016-2020 - Sumantri, Geeta Maharani; Sukartaatmadja, Iswandi (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The stock price is the price formed between supply and demand that occurs in the market. In addition, stock prices reflect the performance of a company which tends to fluctuate in the short term while in the long term good companies tend to increase. When the stock price of a company is high, the value of the company in the eyes of investors is also good and vice versa. The pharmaceutical industry is one of the sectors that has performed well and contributed significantly to the national economy. This study aims to determine the Return On Assets, Current Ratio and Total Asset Turnover on Stock Prices in Pharmaceutical Companies listed on the IDX for the 2016-2020 period either partially, simultaneously or dominantly. The sample in this study were 8 companies obtained by purposive sampling method. The data collection method used is documentation. This study uses Panel Data Regression Analysis, Classical Assumption Test, t-test and F-test using the eviews 12 program. Based on research with a significance level of 0.05, partial results obtained: ROA has no effect and is not significant with a probability value (0.6075 > 0.05). CR has no effect and is not significant with the probability value (0.2601 > 0.05). TATO has a significant effect on the probability value (0.0105 <0.05). Simultaneously ROA, CR and TATO have a significant effect on stock prices with a probability value (0.0000 <0.05). R Square value of 87% is influenced by the above variables while the remaining 13% is influenced by other factors not explained in this study. Keywords: Return On Asset, Current Ratio, Total Asset Turnover and Stock Price